A novel in vitro urethra model to demonstrate bacterial displacement during urinary catheter insertion. Issue 7 (10th July 2020) - J. Cortese, Yvonne; E. Wagner, Victoria; Tierney, Morgan; Scully, David; M. Devine, Declan; Fogarty, Andrew
Abstract : Background: There is currently no standard established in vitro model to test the efficacy of intermittent catheters to prevent or control introduction/movement of bacteria into the urethra during device insertion. This study aimed to address this issue by developing a reproducible agar based in vitro urethral model. Method: A novel in vitro model and testing method was developed to quantify the displacement of bacterial growth after intermittent catheter insertion.The urethral model consists primarily of a preformed channel within a specifically formulated agar based matrix. The urethra model was inoculated at one side of the channel to act as the urethral meatus, a catheter was then inserted. After incubation the bacteria within the urethra channel was quantified. Results: Once optimised, the model produced reliable and reproducible results with both E. coli and S. aureus (P≥0.265). The model was used to test three different intermittent catheter types. When compared to the growth control there was a significant difference in bacterial distribution when inserting an uncoated (P≤0.001) or hydrophilic coated (P≤0.009) catheter; there was no significant difference when a prototype catheter was inserted with either bacterial species used (P≥0.423). Conclusion: These findings support the hypothesis that a single catheter insertion can initiate a catheter-associated urinary tract infection. The in vitro urethra model and associated methodology provide a new research tool for the development and validation of emerging technologies in urological healthcare.